Fungsi Sarkasme dalam Bentuk Umpatan pada Tuturan Masyarakat Kabupaten Kepulauan Meranti - Mangatur Sinaga; Tria Putri Mustika; Muhammad Badrul Tamam (Departement of Mathematics Education, 2023)
This study aims to find out how sarcasm functions in the form of swearing in the speech of the people of the Meranti Islands Regency, especially in Selatpanjang City. In speaking, not all Selatpanjang people speak politely. Polite or not the language used depends on who he communicates with. When using harsh language with people who are close, the other person will not be angry. But if you suddenly speak rudely to someone new, that person might get emotional. The factors that influence the use of the word sarcasm in communication are emotional, spontaneous, disappointed, and social factors. The method used in this study is a qualitative method with data collection techniques through observing, observing, interviewing, recording, and taking notes. The data validation technique used is to increase persistence and triangulation. The analytical method used is to reduce the data and then display the data and draw conclusions from the data analysis that has been done